Unusual sauropod tracks in the Jurassic-Cretaceous transition. Cameros Basin (Burgos, Spain) - Fernández-Baldor, F. Torcida; Díaz-Martínez, I.; Contreras, R.; Huerta, P.; Montero, D.; Urién, V. (Journal of Iberian Geology, 2015)
The Las Sereas site includes at least 14 ichnological outcrops along 5.6 km, in the Lara area, southwest Burgos Province. 67 ichnites of dinosaurs are documented at Las Sereas 7, identified as theropod and sauropod trackways occurring in shallow carbonates of lacustrine environment. Sauropod trackways have intermediate-gauge and low heteropody, and show different anatomical features to other tracks found in the ichnological record, especially in the disposition and orientation of pes digits. They are similar to Polyonyx from the Middle Jurassic of Portugal. However, since they do not preserve reliable manus data they are classified as aff. Polyonyx. The three sauropod trackways are related to the same kind of trackmaker. They differ from each other only in size, and gregarious behavior has not been detected. Analysis of these trackways reveals changes in travel direction even when there are few tracks in each sequence. At the Las Sereas 7 tracksite, the pace length (PL), width of the angulation pattern (WAP) and the WAP/PL ratio and depth analysis via photogrammetry show a direction change in two sauropod trackways. This tracksite and that at La Pedraja are unique in the Tithonian-Berriasian interval of the Iberian Peninsula that occur in a lacustrine environment, and could be indicate of the relationship between the diversity of Iberian, Tithonian-Berriasian sauropod tracks and sedimentary environments.